1993
DOI: 10.1093/ajh/6.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Lone-Term Effects of a Converting Enzyme Inhibitor and a Calcium Channel Blocker on Urinary Albumin Excretion in Patients With Essential Hypertension

Abstract: Microalbuminuria in patients with essential hypertension is associated with increased incidence of cardiovascular morbidity and mortality. Reduction of urinary albumin excretion (UAE) with therapy could reduce cardiovascular events. The long-term effect of commonly used antihypertensive agents on UAE has not been properly investigated. In the present study, we have prospectively studied the effects of therapy for 24 months with a converting enzyme inhibitor, enalapril, or a calcium channel blocker, nicardipine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…36 Which of these factors predominates remains to be established. Unlike previous studies which found no significant effect of dihydropyridine CCBs on UAE, 18,21,22,37,38 in our study we observed a reduction of UAE in the nitrendipine-treated patients, but such an antiproteinuric effect became statistically significant only after 1 year of treatment and was less pronounced as compared to the ramipril induced UAE reduction. This finding suggests two considerations: (a) first, the reduction in UAE from nitrendipine could be mainly attributed to the decrease in systemic BP rather than to other intrinsic effects of the drug, which is supported by the correlation between the UAE and the SBP changes that we found in the nitrendipine but not in the ramipril-treated patients.…”
Section: Discussioncontrasting
confidence: 99%
“…36 Which of these factors predominates remains to be established. Unlike previous studies which found no significant effect of dihydropyridine CCBs on UAE, 18,21,22,37,38 in our study we observed a reduction of UAE in the nitrendipine-treated patients, but such an antiproteinuric effect became statistically significant only after 1 year of treatment and was less pronounced as compared to the ramipril induced UAE reduction. This finding suggests two considerations: (a) first, the reduction in UAE from nitrendipine could be mainly attributed to the decrease in systemic BP rather than to other intrinsic effects of the drug, which is supported by the correlation between the UAE and the SBP changes that we found in the nitrendipine but not in the ramipril-treated patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies had documented the beneficial effect of ACE inhibitors on urinary albumin excretion. 8,21 Clinical beneficial effects of ACE inhibition in microalbuminuric subjects have been well documented 10,11,22 ; however, it is important to realize that these previous studies with diabetic subjects used higher cutoff values than PREVEND IT. The study described by Ravid et al 10 included normotensive Plus-minus values are meanϮSD.…”
Section: Effect Of Ace Inhibitor Interventionmentioning
confidence: 99%
“…105 Further, albeit indirect, evidence for a role of angiotensin II in microalbuminuria development is represented by the stronger anti-albuminuric effect exerted by the ACE inhibitors as compared with other antihypertensive drugs. [42][43][44] Cigarette smoke Similar to type 1 and 2 diabetics, 106,107 non-diabetic smokers, hypertensive or not, tend to excrete more albumin ( Table 5). The first report by Gosling et 114 and may expose to higher risk of morbid events when coexisting with elevated UAE.…”
Section: -99mentioning
confidence: 99%